PWE-230 An iron-responsive probiotic to treat inflammatory bowel disease. (28th May 2012) - Bailey, J; Probert, C; Cogan, T
Abstract : Introduction: Iron is an essential cofactor in most biological systems. Lactic acid bacteria (LAB), frequently employed as probiotics, are unusual in having little or no requirement for iron. In the intestine of inflammatory bowel disease (IBD) patients increased availability of iron following oral iron supplementation or intestinal bleeding enhances growth and virulence of many pathogens against which LAB cannot compete. We have previously identified an iron-responsive LAB, Streptococcus thermophilus NCIMB 41856, with probiotic potential based on functionality in in vitro models which could be competitive during active disease. In order for this strain to be used as a probiotic treatment in IBD patients it must be safe, able to survive gastrointestinal transit and preferentially adhere to epithelial cells and colonise. Methods: Adhesion to the human epithelial cell lines, T84 and Caco-2, was investigated and the ability of S thermophilus NCIMB 41856 to abrogate binding of potential pathogens, in particular adherent-invasive Escherichia coli examined in vitro. The strain was also was subjected to in vitro safety tests which included the production of ammonia, indole, phenols, amines, hydrogen peroxide and D-lactate. Antibiotic resistance was examined, including detection of transmissible antibiotic resistance. Ability to survive within a low pH environment was determined, as was enzyme activity and metabolism of carbohydrates. Results: The strain was found to be capable of binding to epithelial cells and reduce the binding of potential pathogens, while not causing cellular damage itself. It produced no harmful metabolites and no transmissible antibiotic resistance was detected. It has inherent acid resistance and is able to tolerate pH2 with a survival rate of 20%, increasing to 76% at pH3. It is able to metabolise a range of carbohydrates, including lactose, glucose, sucrose, fructose, mannose, ribose, raffinose and N acetyl glucosamine. Conclusion: Our candidate probiotic, S thermophilus NCIMB 41856 has properties that would enable it to survive in and colonise the human intestine. It can survive gastric levels of acidity, utilise a range of carbohydrates present in the intestine, and is able to bind to epithelial cells. It is also able to prevent the binding of potential pathogens. Furthermore, it does not possess undesirable antibiotic resistance or produce harmful metabolic products. These features indicate that it would be safe and potentially effective in use as a probiotic. We propose to test this in vivo in future work. Competing interests: None declared.